Automatic estimation of morphological characteristics of proximal tibia for precise plate treatment using model matching. (April 2020) - Chen, Fang; Zhao, Zhe; Liu, Jia; Cui, Xiwen; Zhang, Daoqiang; Su, Xiuyun; Zhao, Jingxin; Tang, Peifu; Liao, Hongen
Highlights: An automatic method of morphological characters is proposed based on a large-scale library of Chinese tibia models. extensive validation of real clinical cases confirmed that the automatic-estimated morphological characters can help choose well-matched plate for plate treatment. Our method can be easily extended to other applications, including the estimation of morphological characters of femur, fibula and so on. Abstract: Plate treatment is currently the standard treatment of proximal tibia fracture. Morphological characteristics can help orthopedic surgeons understand anatomic information of tibia and choose well-matched plate for reducing difficulties in plate treatment. However, manual measurement of morphological characteristics of patient's tibia is time-consuming and labor-intensive. Therefore, this study proposes an automatic method to accurately estimate the morphological characteristics of patient's tibia for assisting plate treatment. In the off-line stage, an average shape with typical characteristics was computed from 422 tibia models, and the morphological characteristics of the average shape were measured by the orthopedic surgeon. In the on-line stage, the point's correspondence between the average shape and every tibia model was created by the proposed morphable model matching method firstly. Then, the morphological characteristics of tibia for every patient were estimated automatically based on the point's correspondence and characteristics of average shape. The effectiveness of the method was validated by comparing the manual measured and automatic-estimated characteristics. In addition, the basic experiments of virtual and real plate implantation preliminarily confirmed that the automatic-estimated morphological characteristics were helpful for plate treatment. In all, we propose an automatic and accurate estimation method of morphological characteristics for a large-scale library of Chinese tibia models, which provides orthopedic surgeons with scientific and quantitative description of tibia.